Study on Energy Dissipation Characteristic of Ice-Rich Frozen Soil in SHPB Compression Tests - Ma Dongdong; Xiang Huasong; Zhou Zhiwei; Tan Yizhong; Wang Xinpeng (Geofluids)
Frozen soil will inevitably bear dynamic loads (impact and blasting) in the construction process in cold regions; the investigation of dynamic energy dissipation characteristic of ice-rich frozen soil is beneficial to optimize blasting parameters and the design of underground explosion-proof structure. In this study, the dynamic impact laboratory tests were conducted for frozen sandy soil with various water contents (from 15% to 110%) and strain rates (from 450 s-1 to 728 s-1) based on the split Hopkinson pressure bar (SHPB) system. The influences of strain rate, temperature, and water content on the energy parameters (i.e., absorption energy, reflected energy, and absorption energy rate) were systematically analyzed. Moreover, the energy dissipation characteristics of frozen sandy soil under different deformation stages were studied. Test results revealed that under impact load, the proportion of reflected energy to incident energy was the largest for frozen soil materials. Both the absorption energy and reflected energy were associated with strain rate. However, compared with the water content and temperature, the sensitivities of strain rate on the absorption energy rate were not obvious. At -10°C, the average absorption energy rate decreases from 17.6% to 14.5% when the water content increases from 15% to 37.5%, with a reduction of 18%. However, it substantially decreases to 6.9% at 45% water content, with a large-scale reduction of 61% compared with that at 15% water content. The energy dissipation parameters (i.e., absorption energy, releasable elastic strain energy, and dissipation energy) were closely associated with the water content, temperature, and strain rate.